Growth and economic performance of Kacang goats fed concentrates containing cattle rumen content silage (Journal of Advanced Veterinary and Animal Research, 2026)
Objective: This study aimed to determine the growth and economic efficiency of Kacang goats that were fed different levels of cattle rumen content silage (CRCS) in a concentrate ration based on Andropogon timorensis grass. Materials and Methods: Twenty male Kacang goats aged 8–10 months, with an average live weight of 11.7 ± 1.4 kg, were used as experimental animals. The treatment applied was the use of CRCS in the concentrate at different levels: 0% (T0), 10% (T1), 20% (T2), and 30% (T3). The feed consisted of 70% A. timorensis grass and 30% concentrate. Each treatment was repeated five times, resulting in 20 experimental units. The parameters measured were dry matter intake (DMI), daily weight gain (DWG), feed conversion ratio (FCR), feed cost per gain (FCPG), and income over feed cost (IOFC). The data were analyzed using analysis of variance and further tested with Duncan’s multiple range test. Results: The results showed that the treatment had no significant effect (p > 0.05) on DMI, while DWG, FCR, FCPG, and IOFC were significantly affected (p < 0.05) by the treatment. The use of 10% CRCS (T1) resulted in significantly higher (p < 0.05) DWG (38.20 gm/day), FCR (8.33), FCPG (40.57), and IOFC (Indonesian rupiahs 30,001) compared to T2 and T3, but was not significantly different (p > 0.05) from T0. Conclusions: The use of 10% CRCS in concentration improves the growth and economic efficiency of Kacang goats and provides sustainable benefits to the environment by utilizing CRCS in feed rations.J. Adv. Vet. Anim. Res., 12(4): 1363–1369, December 2025http://doi.org/10.5455/javar.2025.l996